Switching Costs in Infinitely Repeated Games - Barton Lipman; Ruqu Wang (Queen's University, Department of Economics, 2006)
We show that small switching costs can have surprisingly dramatic effects in infinitely repeated games if these costs are large relative to payoffs in a single period. This shows that the results in Lipman and Wang [2000] do have analogs in the case of infinitely repeated games. We also discuss whether the results here or those in Lipman and Wang [2000] imply a discontinuity in the equilibrium outcome correspondence with respect to small switching costs. We conclude that there is not a discontinuity with respect to switching costs but that the switching costs do create a discontinuity with respect to the length of a period.
Keywords: C72; 330; infinite horizon; repeated games; switching costs; Folk Theorem; Wiederholte Spiele; Wechselverhalten; Theorie